'Smartscopy' as an alternative device for cervical cancer screening: a pilot study. Issue 2 (30th March 2017) - Tanaka, Yusuke; Ueda, Yutaka; Okazawa, Akiko; Kakuda, Mamoru; Matsuzaki, Shinya; Kobayashi, Eiji; Yoshino, Kiyoshi; Kimura, Tadashi
Abstract : The use of smartphones, mobile networks and associated health applications (known as apps) is now almost universal. Countries with low medical resources need assistance in their delivery of healthcare. This is particularly true where there are limited numbers of specialised physicians or nurses with respect to cancer screening. As smartphones become more universal, real-time and near-real-time expert medical consultations and telediagnosis are becoming more common. This leads us to believe that there will soon be a demand for mobile cancer screening services, which will be particularly useful for women living in rural areas or doctor-less inner city communities. The smartphone would seem to have almost limitless possibilities to address this need. As a first step in studying how cervical cancer screening using a smartphone could have widespread implementation, we conducted a pilot study to evaluate the utility of a smartphone to diagnose cervical intraepithelial neoplasm or invasive cervical cancer in 20 patients having an abnormal cervical cytology. Our results indicate that continuing progress in digital imaging devices may allow the quality of cervical cancer screening to be improved.